PENGARUH KADAR PEREKAT UREA FORMALDEHIDA DAN UKURAN PARTIKEL LIMBAH KAYU MERBAU (intsia bijuga) TERHADAP SIFAT FISIS DAN MEKANIS PAPAN PARTIKEL - , Slamet Dwiyono, Dr. Eng. Iman aryanto, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The forest area of Papua Province area of 40,487,130.09 acres or 95% of the total land area is a potential producer of merbau (Intsia bijuga) and opportunity to be utilized optimally as an asset for local revenues, both from its function as a protected area or a combination of conservation for production interests. The purpose of this study is to investigate the effect of optimization levels of urea formaldehyde adhesive 6%, 8%, 10% and 12% with particle size merbau wood waste 2 mm sieve, and a 5 mm sieve but retained on the sieve of 2 mm, against nature physical and mechanical particle board. This study used a factorial method which consists of two factors. The first factor had four levels of treatment that is gluten content of 6% (P1), 8% (P2), 10% (P3) and 12% (P4) and the second factor has two levels of treatment that is the size of particles that escape the 2 mm sieve size (U1) and the particles that pass in the 5 mm sieve but retained on sieve size of 2 mm (U2), which is arranged in complete randomized design (CRD) and repeated three times. The tested physical properties of density, water absorption, development of thick, were tested for mechanical properties of tensile strength perpendicular / internal bonding (IB), modulus of elasticity (MOE) and modulus of rupture (MOR). The observation was analyzed by ANOVA (analysis of variance) at 5% significance level with the application of SPSS (Statistical Package for Social Sciences), the results obtained showed that the larger particle size and greater number of adhesive will significantly affect the physical and mechanical properties of boards particles. The best properties are generally owned by a particle board with adhesive content of 12% with merbau wood particle composition with size caught in the sieve of 2 mm and 5 mm sieve pass on (U2.P4).The highest density of 0.744 g/cm3, the highest water absorption of 37.88%, the highest thick development of 0.607%, Internal bonding 4.547 kg / cm ², fracture modulus 99,695 kg / cm ², modulus elastis12.648, 62 kg / cm ². The larger particle size will be more dense, water-resistant, increase density, reduce the absorption of water and heavy development and to improve the mechanical properties of particle board. More and more the amount of adhesive physical and mechanical properties of particle board, the better.